Extraction of Co(II) and Ni(II) from concentrated HCl solutions using Alamine 336 - SAYAR, NİHAT ALPAGU (ELSEVIER, 2009)
Extraction of Co(II) and Ni(II) from aqueous HCl solutions into organic Alamine 336-m-xylene systems were studied. Extraction experiments were repeated for three initial metal concentration ratios with total initial metal concentration of 7 g L-1, each at 1, 5 and 10 M HCl. The extraction percentage, E, in terms of volume percentage of Alamine content, V, in solvent mixture, were determined for each metal. Optimal Alamine 336 contents were reported for a single stage extraction. The amine loading factor and separation factor values were also determined in terms of V-e. Alamine 336 was found to be a suitable extracting and separating agent for Co(II)-Ni(II) containing solutions at 5 M HCl. (C) 2008 Elsevier B.V. All rights reserved
Keywords: Solvent extraction; Nickel; Cobalt; Alamine 336; Chloride media; SUBSTITUTED OXIME EXTRACTANTS; HYDROCHLORIC-ACID SOLUTIONS; SOLVENT-EXTRACTION; SULFATE-SOLUTIONS; CHLORIDE SOLUTIONS; SODIUM-SALTS; NICKEL; COBALT; SEPARATION; CYANEX-272